PERAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Irham. M; Nur Aina (PT. Hasba Edukasi Mandiri, 2025)
Education is very important as one of the main foundations in developing human potential has a significant impact on the progress of a country. The future of the nation depends on the quality of education applied in the current era. High quality education can be realized if educational institutions seriously pay attention to the quality of education. The decline in the quality of education in Indonesia occurs in the input and process aspects of education. One of the causes is the lack of quality, competence, and professionalism of the majority of madrasah principals. Therefore, an important step to improve the quality of education is to empower the role of madrasah principals. Madrasah principals have a central role as a driver of overall school productivity activities that depend heavily on the quality of leadership of the madrasah principal. Therefore, the purpose of this study is to determine the role of madrasah principals in improving the quality of education in (Madrasah Ibtidaiyah ‎Nurul Ihsan Village ‎Mangun Jayo District Tebo Tengah Regency Tebo. This research was conducted using a qualitative descriptive approach. The subjects involved the Principal, Islamic Religious Education Teachers, Students, and parents. Data were collected through observation and interviews. The data were analyzed qualitatively descriptively using reduction methods, data review, and conclusion drawing. The results of the study indicate that the role of the principal in improving the quality of education is carried out through several efforts, such as developing curriculum administration, facilities and infrastructure, human resources, and community participation. Inhibiting factors include a lack of personnel appropriate to the subjects taught and a lack of professionalism of teachers in making plans. Supporting factors include new ideas in creating a good learning atmosphere.